2019
DOI: 10.1021/acssuschemeng.8b06723
|View full text |Cite
|
Sign up to set email alerts
|

trans-Resveratrol and trans-ε-Viniferin in Grape Canes and Stocks Originating from Savoie Mont Blanc Vineyard Region: Pre-extraction Parameters for Improved Recovery

Abstract: Viticultural by-products are known to contain high-value compounds such as stilbenes. Wine sector in Savoie Mont Blanc region (France) generates high amount of waste including grape canes and grapevine stocks that remain unvalued. Herein, the potential of the most widespread grapevine varieties in Savoie Mont Blanc territory, Jacquère and Mondeuse, as sources of two stilbenes, trans-resveratrol (Rsv) and trans-ε-viniferin (Vf) was investigated for the first time. Using the reported extraction technique, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 39 publications
1
21
2
Order By: Relevance
“…Other studies have reported lower values with respect to our data for ϵ ‐viniferin, ranging from 2600 to 3300 μg g −1 DW in Sauvignon Blanc canes, 2200 μg g −1 DW in Cabernet Sauvignon, 1900 μg g −1 DW in Merlot, 1300 μg g −1 DW in Chardonnay, 2600 μg g −1 DW in Malbec and 3700 μg g −1 DW in Pinot Noir . Zwingelstein et al . reported values of ϵ ‐viniferin ranging from 1620 to 6667 μg g −1 DW in French grape varieties.…”
Section: Resultscontrasting
confidence: 92%
See 2 more Smart Citations
“…Other studies have reported lower values with respect to our data for ϵ ‐viniferin, ranging from 2600 to 3300 μg g −1 DW in Sauvignon Blanc canes, 2200 μg g −1 DW in Cabernet Sauvignon, 1900 μg g −1 DW in Merlot, 1300 μg g −1 DW in Chardonnay, 2600 μg g −1 DW in Malbec and 3700 μg g −1 DW in Pinot Noir . Zwingelstein et al . reported values of ϵ ‐viniferin ranging from 1620 to 6667 μg g −1 DW in French grape varieties.…”
Section: Resultscontrasting
confidence: 92%
“…It was found at levels of between 6 (CH) and 250 μg g −1 (CS2), in accordance with the published data . However, the results obtained in the present study for trans ‐resveratrol were lower than in other reports, with values ranging from 122 to 7306 μg g −1 . Higher levels of trans ‐resveratrol than ϵ ‐viniferin may be a result of the influence of storage conditions (time, temperature, sample treatment) of canes .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…It has already been demonstrated that, after cutting, grape canes if stored properly over some months, accumulate large quantities of stilbenoid . This increase depends on storage time, temperature, relative moisture during storage, grape variety, size of cane pieces during storage, and whether the grapes were cultivated using a conventional or organic mode . However, the combined effect of pruning and storage time on the stilbene accumulation rate has not been studied before.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, the antimicrobial properties of stilbenes have been investigated less. Due to its significance in both plant protection and human health, the content and distribution of resveratrol in grape and wine, and in the by‐products from grape and wine production, has attracted increasing attention in recent years …”
Section: Introductionmentioning
confidence: 99%